The Endoscopic Treatment of Tracheo-bronchial Amyloidosis: A Challenging Issue - Umberto Caterino; Sandro Batzella; Gabriele Lucantoni; Alfonso Fiorelli; Mario Santini; Giovanni Galluccio (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2015)
Tracheo-bronchial amyloidosis is a rare airway disorder that can be a challenge for the limitations of  treatment,  recurrence  and  complications.  We  report  the  complex  clinical  course  of  a  patient  with symptomatic  localized  tracheo-bronchial  amyloidosis.  Different  procedures  were  performed  due  to recurrent amyloid over a period of three and half years from the first endoscopic resection